Conducting Assessment Workshop for Staff Development Program - Zainal Abidin, Azizan (2009)
Universiti Teknologi PETRONAS is a private university situated in Perak, Malaysia offers Engineering and Technology Programs. The faculty members are from the departments of Electrical and Electronics Engineering, Mechanical Engineering, Chemical Engineering, Civil Engineering, Petroleum Engineering, Computer and Information Sciences, and Management and Humanities. Regardless of their teaching experiences, newly recruited faculty members are required to participate in the Education Delivery and Assessment Workshop, organized by the Academic Central Services Department in collaboration with the Human Resource Department. Most of these new faculty members have undergone no formal teaching training and depend primarily on their past teaching experiences gained from previous institutions of higher learning they were affiliated with. But for those coming from the industries, it is a new experience altogether. Yet, these lecturers will be expected to teach at the start of the semester, and their performance in class is subjected to evaluation by the students whom they teach. What kind of education delivery and assessment methods preparation are in store for them? The Academic Central Services Department plays an important role in providing in-house training with the main objective of the training; to serve as a means of introducing the education delivery and assessment culture that meet the standards set by the university. It is made compulsory for all new faculty members of this university to undergo the Staff Development Program. This program also acts as a refresher course for a few lecturers whose evaluations have yet to meet the minimum standard measurement. The program is effectively an Education Delivery and Assessment workshop conducted by the university’s trained facilitators who are senior faculty members with consistently good teaching track record, typically identified by the university. The objective of this paper is to share the experience of how the in-house assessment training session is conducted and the outcomes of the training. A pretest and a posttest are dispensed to measure if the learning outcomes of the workshop have been achieved. A questionnaire issued by the Human Resource Management Department is also used to obtain feedback from the workshop participants. The results obtained are encouraging and show that the training on assessment methods has given a promising impact.